Lightweight polyurethane-filled tire and method of manufacture and use
By constructing a composite network of carboxylated cellulose nanocrystals and para-aramid nanofibers in polyurethane-filled tires and utilizing the reversible crosslinking of metal cations and carboxylate groups, the problems of insufficient load-bearing capacity and poor durability of lightweight tires were solved, achieving a high-performance lightweight effect.
Patent Information
- Application Number
- CN202611040381.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-11-06
AI Technical Summary
Existing polyurethane-filled tires suffer from insufficient load-bearing capacity, brittleness, and poor durability during the lightweighting process, especially at low densities where it is difficult to maintain high load-bearing capacity and tear resistance.
A composite nanofiber network is formed by combining carboxylated cellulose nanocrystals and para-aramid nanofibers to encapsulate lightweight microspheres and form a non-covalent cross-linked network with metal cations, thereby constructing a honeycomb-like wall structure to enhance the material's stiffness and crack propagation resistance.
It achieves excellent tear resistance and dynamic durability of low-density polyurethane filled tires under high loads, dissipates mechanical energy through reversible metal-carboxylate coordination bonds and provides self-healing capability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire technology, specifically to a lightweight polyurethane-filled tire, its preparation method, and its application. Background Technology
[0002] Polyurethane-filled tires are widely used in low-speed, high-load applications such as forklifts, loaders, and mining vehicles due to their advantages such as being airless, puncture-resistant, and having customizable load-bearing capacity. To reduce weight, existing technologies often employ chemical foaming or the addition of lightweight fillers. Chemical foaming suffers from difficulty in precisely controlling the pore structure, and the poor mechanical properties of the pore walls make the foam filler material prone to permanent deformation and cracking under repeated compression. While directly adding hollow microspheres can reduce weight, the weak interfacial bonding between the microspheres and the matrix leads to interfacial debonding under dynamic loads, causing crack initiation and propagation, resulting in a significant decrease in the material's load-bearing capacity, tear resistance, and fatigue life. Alternatively, adding short fibers to the matrix to reinforce lightweight composite materials is another option, but fiber dispersion is difficult, and fiber agglomeration is common. Furthermore, the fiber-matrix relationship is merely a simple physical interlocking structure, failing to establish an effective stress transfer and energy dissipation mechanism. Therefore, this application achieves significant weight reduction in polyurethane-filled tires while ensuring high load-bearing capacity, excellent tear resistance, and dynamic durability at low density, thus addressing the technical problems of existing technologies. Summary of the Invention
[0003] This invention addresses the shortcomings of existing technologies by providing a lightweight polyurethane-filled tire, its preparation method, and its application, effectively solving the problems of insufficient load-bearing capacity, brittleness, and poor durability of traditional lightweight porous materials.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A lightweight polyurethane-filled tire includes a tire carcass and a polyurethane elastomer composite material filled inside the carcass, characterized in that the polyurethane elastomer composite material comprises: A polyurethane matrix, wherein the polyurethane matrix contains metal cations; A composite nanofiber network uniformly dispersed in the polyurethane matrix is formed by the self-assembly of carboxylated cellulose nanocrystals and para-aramid nanofibers through hydrogen bonding and / or electrostatic interaction, and the composite nanofiber network is wrapped around the surface of lightweight microspheres to form a honeycomb-like wall structure. The surface of the carboxylated cellulose nanocrystals is rich in carboxylate groups; the metal cations form coordination bonds with the carboxylate groups on the surface of the carboxylated cellulose nanocrystals to form a non-covalent crosslinked network in the polyurethane elastomer composite material.
[0005] Preferably, the carboxylated cellulose nanocrystals are prepared by selectively oxidizing the primary hydroxyl groups at the C6 position on the surface of the cellulose nanocrystals to sodium carboxylate groups through a TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical) oxidation system.
[0006] Preferably, the para-aramid nanofibers are prepared by deprotonating and exfoliating para-aramid fibers in a dimethyl sulfoxide / potassium hydroxide (DMSO / KOH) system to obtain para-aramid nanofibers with a diameter of 5-30 nm and an aspect ratio greater than 500, and the surface of the nanofibers retains amide groups.
[0007] Preferably, the lightweight microspheres are selected from one or a combination of two types: the first type is expanded thermoplastic polymer microspheres with a shell of vinylidene chloride-acrylonitrile copolymer, a particle size of 20~100μm, and a density of 0.1~0.2g / cm³. 3 ; The second type consists of hollow glass microspheres or hollow ceramic microspheres, with a particle size of 10~80μm and a density of (0.15~0.4)g / cm³. 3 The compressive strength is greater than 20 MPa.
[0008] Preferably, the metal cation is Zn. 2+ Ca 2+ Mg 2+ Fe 3+ Or Al 3+ One or more of the following; the metal cation is introduced in the form of acetylacetone salt, chloride or sulfate.
[0009] Preferably, the polyurethane matrix is prepared by reacting an isocyanate prepolymer with a curing agent component, wherein the isocyanate prepolymer is a reaction product of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, or isophorone diisocyanate with a polyether polyol or a polyester polyol.
[0010] Preferably, the mass ratio of the carboxylated cellulose nanocrystals to the para-aramid nanofibers is 1:(0.5~5), the total mass of the composite nanofiber network accounts for 1%-10% of the total mass of the polyurethane elastomer composite material, and the volume of the lightweight microspheres accounts for 20%-60% of the total volume of the polyurethane elastomer composite material.
[0011] The second objective of this invention is to provide a method for preparing the aforementioned lightweight polyurethane-filled tire, comprising the following steps: (1) Preparation of carboxylated cellulose nanocrystals: Cellulose nanocrystals were dispersed in water to form a suspension. Under the conditions of TEMPO / sodium bromide / sodium hypochlorite oxidation system, pH 9-11, and room temperature, the primary hydroxyl groups at the C6 position on the surface of the nanocrystals were selectively oxidized to sodium carboxylate groups. After dialysis and freeze drying, carboxylated cellulose nanocrystals were obtained. (2) Preparation of para-aramid nanofibers: Para-aramid short-cut fibers were added to a dimethyl sulfoxide / potassium hydroxide (DMSO / KOH) system and stirred under nitrogen protection at room temperature for deprotonation exfoliation. After precipitation and washing, a para-aramid nanofiber suspension was obtained. (3) Constructing a composite nanofiber network and coating lightweight microspheres: The carboxylated cellulose nanocrystal suspension obtained in step 1 and the para-aramid nanofiber suspension obtained in step 2 are mixed at a mass ratio of 1:(0.5~5) and ultrasonically treated at pH 8~9 to allow the carboxylated cellulose nanocrystals and para-aramid nanofibers to self-assemble into a composite nanofiber network through hydrogen bonding and / or electrostatic interaction; lightweight microspheres are added under stirring to allow the composite nanofiber network to adsorb and coat the surface of the lightweight microspheres, and the carboxylated cellulose nanocrystals and para-aramid nanofibers complement each other to form a fiber shell. The fiber shells on the surfaces of adjacent microspheres are interconnected to form a precursor slurry with a honeycomb-like structure; the slurry is vacuum dried to obtain the composite microsphere filler; (4) Preparation of polyurethane elastomer composite material and filling of tire: The composite microsphere filler obtained in step 3 is mixed evenly with the curing agent component containing metal cations, isocyanate prepolymer is added, vacuum stirring is performed to remove bubbles, and the mixture is injected into a mold placed in the tire cavity and heated to cure. During the curing process, the metal cations form coordination bonds with the carboxylate groups on the surface of carboxylated cellulose nanocrystals to form a non-covalent cross-linked network, thus obtaining the lightweight polyurethane filled tire.
[0012] Preferably, the curing temperature in step (4) is 60~90℃ and the curing time is 12~48 hours.
[0013] The third objective of this invention is to provide an application of the aforementioned lightweight polyurethane-filled tire in low-speed, high-load-bearing vehicles, including forklifts, loaders, mining dump trucks, or airport ground support vehicles.
[0014] Compared with the prior art, the advantages of the present invention are as follows: (1) In this invention, a composite nanofiber network composed of carboxylated cellulose nanocrystals and para-aramid nanofibers is formed to encapsulate microspheres like a honeycomb wall and penetrate the matrix to form a three-dimensional skeleton, which makes the low-density material have excellent compressive modulus and strength; the coordination cross-linking network formed by metal cations and carboxylate groups further improves the overall structural stiffness. (2) The composite nanofiber network of the present invention can effectively prevent the propagation of cracks, and the metal-carboxylate coordination bond, as a reversible sacrificial bond, preferentially dissociates under load, dissipates a large amount of mechanical energy, and can be reassembled after unloading, giving the material self-healing ability and excellent fatigue resistance. (3) The composite nanofiber network of the present invention physically self-assembles and tightly encapsulates the microspheres, and the carboxylate groups on the fiber surface participate in matrix crosslinking, thus eliminating the weak interface problem in traditional composite materials. Detailed Implementation
[0015] The technical solution of the present invention will be described in detail below with reference to embodiments. To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0016] The present invention will be further described in detail below through examples and comparative examples, but the present invention is not limited to these examples. All raw materials used in the examples and comparative examples are commercially available products.
[0017] Cellulose nanocrystals (CNC), prepared by sulfuric acid hydrolysis, with diameters of 5–20 nm and lengths of 100–500 nm, serve as the basic raw material. TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical), with a purity of not less than 98%, is used as a catalyst for the catalytic oxidation reaction. Sodium bromide (NaBr), analytical grade, is used as a co-catalyst. Sodium hypochlorite solution (NaClO), with an available chlorine content of 10%–15%, serves as the primary oxidant. Sodium hydroxide (NaOH), analytical grade, is prepared as a 0.5 M solution to maintain the pH of the reaction system at 10.0–10.5. Hydrochloric acid (HCl), analytical grade, is prepared as a 0.1 M solution for neutralization after the reaction. Anhydrous ethanol, analytical grade, is used as a reaction terminator. Dialysis bags, with a molecular weight cutoff of 3500, are used to purify the product.
[0018] Para-aramid chopped fibers, such as Kevlar, can be selected. ® Brand, length 1-3mm, is the basic raw material. Dimethyl sulfoxide (DMSO), anhydrous grade, purity not less than 99.9%, is used as a solvent. Potassium hydroxide, analytical grade, in flake or powder form, is used as a deprotonating reagent.
[0019] The isocyanate prepolymer, as component A, can be of the diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or isophorone diisocyanate (IPDI) type, prepared by pre-reaction of the corresponding isocyanate monomer with polyether polyol or polyester polyol. Among them, the MDI type has high reactivity and good mechanical strength; the TDI type has good flexibility; and the HDI and IPDI types have excellent resistance to yellowing.
[0020] The curing agent component (component B) comprises a polyether polyol, a chain extender, and a catalyst. The polyether polyol can be polytetrahydrofuran ether diol (PTMEG, number average molecular weight approximately 2000) or polypropylene triol (number average molecular weight approximately 4800). The chain extender is 1,4-butanediol (BDO), analytical grade. The catalyst is dibutyltin dilaurate (DBTDL), with a purity of not less than 95%.
[0021] The metal cation is introduced in the form of a metal salt and pre-dissolved in the curing agent component. Zinc acetylacetonate is preferred, with a purity of not less than 98%, as its zinc ions can form stable coordination crosslinks with carboxylate groups. Iron acetylacetonate, calcium acetylacetonate, magnesium acetylacetonate, or aluminum acetylacetonate can also be used, all with a purity of not less than 95%. Inorganic salt forms, such as zinc chloride or zinc sulfate heptahydrate, can also be used.
[0022] Lightweight microspheres can be selected from one or a combination of the following three types: The first type is expanded thermoplastic polymer microspheres, such as Expancell 920 DE 40 d30, with a shell of vinylidene chloride-acrylonitrile copolymer, a particle size range of 20~100μm, and a density of 0.10~0.20g / cm³. 3 The second type consists of hollow glass microspheres, such as 3M S60HS or equivalent, with a particle size range of 10~80μm and a density of 0.15~0.40g / cm³. 3 The compressive strength is greater than 20 MPa. The third type is hollow ceramic microspheres, commercially available, with a particle size range of 10~80 μm and a density of 0.20~0.40 g / cm³. 3 The compressive strength is greater than 20 MPa.
[0023] Preparation Example 1: Preparation of Carboxylated Cellulose Nanocrystals (i-CNC) 10 g of cellulose nanocrystals (CNC) were dispersed in 1000 mL of deionized water and sonicated for 30 minutes. 0.16 g of TEMPO and 1.0 g of NaBr were added and stirred to dissolve. NaClO solution was slowly added dropwise at room temperature in the dark, with an available chlorine to cellulose nanocrystal mass ratio of 5 mmol / g. The pH was adjusted to 10.0–10.5 with 0.5 M NaOH, and the reaction was allowed to proceed for 4 hours. The reaction was terminated by adding 10 mL of ethanol, neutralized with dilute hydrochloric acid, dialyzed (molecular weight cutoff 3500) for 72 hours, and then freeze-dried to obtain TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical) oxidized carboxylated cellulose nanocrystals (i-CNC-COOH), with a carboxyl content of approximately 1.4 mmol / g.
[0024] Preparation Example 2: Preparation of para-aramid nanofibers (ANF) 5.0 g of chopped para-aramid fibers (Kevlar, 1-3 mm in length) were added to 500 mL of a dimethyl sulfoxide solution containing 1.5 g of KOH and stirred for 7 days at room temperature under nitrogen protection. The resulting dark red viscous liquid was slowly poured into a large amount of deionized water, filtered, and repeatedly washed until neutral to obtain an aqueous suspension of para-aramid nanofibers with a solid content of approximately 0.5 wt%, fiber diameter of 10-20 nm, and aspect ratio >600.
[0025] Example 1: The steps for preparing the tire filler material in this example are as follows: (1) The carboxylated cellulose nanocrystals of Preparation Example 1 and the para-aramid nanofibers of Preparation Example 2 were mixed at a solid mass ratio of 1:2 (total 5g), sonicated for 30 minutes, and the pH was adjusted to 8.5 with dilute NaOH to form a homogeneous hybrid colloid. 20g of expanded thermoplastic microspheres were slowly added, stirred for 30 minutes, and dried under vacuum at 60°C to obtain the composite microsphere filler. The expanded thermoplastic microspheres were Expansionl 920 DE 40 d30 with a density of 0.13 g / cm³. 3 Particle size 30~60μm; (2) Mix the above-mentioned composite microsphere filler with component B (containing polyoxypropylene triol Mn=4800, 1,4-butanediol and zinc acetylacetonate accounting for 2% of the total mass) evenly, then add MDI type isocyanate prepolymer at an NCO / OH molar ratio of 1.05, with an NCO mass fraction of 15%, vacuum stir to remove bubbles, inject into the tire cavity of the tire carcass mold, cure at 80°C for 24 hours, and demold to obtain the final product.
[0026] The composite material contains 5% nanofibers by mass, 40% microspheres by volume, and a density of 0.58 g / cm³. 3 .
[0027] Example 2: The difference from Example 1 is that the metal cation used is Fe. 3+It is introduced with acetylacetone iron, and the amount used is 1.5% of the total mass.
[0028] The density of the obtained tire filler material is 0.59 g / cm³. 3 .
[0029] Example 3: The difference from Example 1 is that the lightweight microspheres used are hollow glass microspheres (S60HS, 3M, density 0.60 g / cm³). 3 (Compressive strength > 124 MPa), the addition amount is adjusted to 30% by volume.
[0030] The density of the composite material is 0.67 g / cm³. 3 .
[0031] Example 4: The difference from Example 1 is that the mass ratio of carboxylated cellulose nanocrystals to para-aramid nanofibers is adjusted to 1:5, the total nanofiber mass ratio is 8%, and the volume ratio of lightweight microspheres is 50%.
[0032] The density of the obtained material is 0.52 g / cm³. 3 .
[0033] Example 5: The difference from Example 1 is that the curing temperature is 90℃ and the curing time is 12 hours. The density of the resulting tire filler material is 0.58 g / cm³. 3 .
[0034] Comparative Example 1 (without nanofiber network): Thermoplastic microspheres were directly added to the polyurethane formulation at 40 vol% (containing the same amount of zinc acetylacetone as in Example 1), without adding any nanofibers.
[0035] The density of the obtained material is 0.55 g / cm³. 3 .
[0036] Comparative Example 2 (using unmodified cellulose nanocrystals and para-aramid nanofibers composite): The carboxylated cellulose nanocrystals in Preparation Example 1 were replaced with an equal amount of unoxidized cellulose nanocrystals (the surface contains only -OH, without -COO). - The remaining steps are the same as in Example 1. Since there is no -COO - Group, Zn 2+ An effective ion cross-linking network cannot be formed.
[0037] Comparative Example 3 (using only para-aramid nanofibers, without carboxylated cellulose nanocrystals): without adding carboxylated cellulose nanocrystals, only para-aramid nanofibers (equal to the total nanofiber mass) were used for microsphere coating, and the remaining steps were the same as in Example 1.
[0038] Comparative Example 4 (using only carboxylated cellulose nanocrystals, without para-aramid nanofibers): No para-aramid nanofibers were added, and only carboxylated cellulose nanocrystals were used for microsphere coating. The remaining steps were the same as in Example 1.
[0039] Comparative Example 5 (using an irreversible covalent crosslinking agent instead of metal ion coordination): In the formulation of Example 1, instead of zinc acetylacetonate, dicumyl peroxide at 1% of the polymer matrix mass was added as a free radical crosslinking agent to form permanent covalent crosslinks during the curing process. The remaining steps and components were the same as in Example 1.
[0040] Comparative Example 6 (Traditional Solid Polyurethane Filled Tire): Made of high-density solid polyurethane, cured from polytetrahydrofuran ether diol (PTMEG) / diphenylmethane diisocyanate (MDI) prepolymer and butanediol, without any lightweight fillers or nanofibers, with a density of 1.05 g / cm³. 3 .
[0041] Performance testing methods: 1. Density Test according to GB / T 6343; cut a regular-shaped sample (e.g., 50mm × 50mm × thickness), weigh it in air using an analytical balance, accurate to 0.1mg; measure the sample dimensions with vernier calipers, and calculate the volume V; density = m / V (g / cm³) 3 Each group should contain no fewer than 5 samples, and the average value of the results should be taken.
[0042] 2. Compression modulus Test according to GB / T 7757; use type A specimen (cylinder with a diameter of 29.0 mm and a height of 12.5 mm); place the specimen in the center of the compression fixture of the universal testing machine and apply a compressive load at a speed of 2 mm / min; record the stress-strain curve, and take the slope of the curve in the strain range of 0.05% to 0.25% as the compressive modulus (MPa); test 5 specimens in each group and take the average value.
[0043] 3. Compressive strength (10% strain compressive stress) Test according to GB / T 7757; the specimen specifications are the same as those for the compression modulus test (cylinder with a diameter of 29.0 mm and a height of 12.5 mm); compress the specimen at a speed of 2 mm / min to 10% of the original height at strain, and record the compressive stress value at this point, which is the 10% compressive strength (MPa); test 5 specimens in each group and take the average value.
[0044] 4. Tear strength Test according to GB / T 529; use right-angled specimens (without notches), specimen thickness 2.0±0.2mm, cut according to standard; clamp the specimens on a universal testing machine and perform tensile tearing at a speed of 500mm / min; record the maximum force F during the tearing process; tear strength = F / d (d is the specimen thickness, mm), the result is expressed as kN / m; test 5 specimens in each group and take the median.
[0045] 5. Cyclic compression set Test according to GB / T 7759.1; use type B specimen (cylinder with a diameter of 13.0 mm and a height of 6.3 mm), and measure the initial height h0; put the specimen into the compression device and apply pressure to compress its height to 75% of the initial height (i.e., compression ratio of 25%); perform 100,000 cycles of compression at room temperature (23±2℃) and a frequency of 2 Hz; after the cycle, take out the specimen, let it recover in a free state for 30 minutes, and measure the height h1 after recovery; compression permanent deformation rate = (h0-h1) / h0×100%.
[0046] Table 1: Test results of mechanical properties of the filler materials in the examples
[0047] Table 2: Test results of mechanical properties of filler materials in comparative examples
[0048] Based on the table above: (1) Compared with Comparative Example 1, after adding the composite nanofiber network, the compressive modulus increased from 8.2 MPa to 28.6 MPa, and the tear strength increased from 8.5 kN / m to 42.3 kN / m, both of which were significantly improved. At the same time, the permanent deformation rate decreased significantly from 45% to 15%. This shows that the rigid structure formed by the carboxylated cellulose nanocrystal / para-aramid nanofiber network on the surface of the microspheres can efficiently transfer the stress of the polyurethane elastomer composite material.
[0049] (2) Comparative Example 2 used carboxyl-free cellulose nanocrystals, which could not form metal ion coordination crosslinks. Its compressive modulus (13.5 MPa) and tear strength (18.2 kN / m) were much lower than those of Example 1, while its permanent deformation rate was significantly increased. This indicates that the metal-carboxylate coordination network can improve the compressive modulus and stability of polyurethane elastomer composites.
[0050] (3) Comparative Example 3 used only para-aramid nanofibers and Comparative Example 4 used only carboxylated cellulose nanocrystals. The mechanical properties of both comparative examples were significantly weaker than those of Example 1. This indicates that carboxylated cellulose nanocrystals can provide ionic crosslinking sites and whisker reinforcement, while para-aramid nanofibers can provide long-range bridging and skeletal support. The two have a significant synergistic effect and are indispensable.
[0051] (4) Comparative Example 5 uses permanent covalent crosslinking instead of ionic coordination crosslinking. Although the initial compressive modulus can reach 22.1 MPa, the tear strength of 25.4 kN / m and dynamic permanent deformation of 35% are significantly inferior to those of Example 1. This is because covalent bonds cannot be recovered after compression damage, and microcracks in the material gradually accumulate; while the reversible fracture-reorganization of metal coordination bonds can dissipate energy and repair damage.
[0052] The coordination bonds formed between metal cations and carboxylate groups on the surface of carboxylated cellulose nanocrystals have significantly lower bond energies (50–120 kJ / mol) than covalent bonds (200–400 kJ / mol). Under dynamic loading, these bonds preferentially undergo reversible dissociation, acting as sacrificial bonds. The fracture process consumes mechanical energy and converts it into heat energy, while simultaneously releasing hidden chain segment length for further energy absorption. After the load is removed, driven by the entropic elasticity of the polymer matrix, the dissociated metal ions and carboxylate groups spontaneously recombine within the confined space of the nanofiber network, repairing the cross-linked network. This reversible fracture-reconstitution mechanism endows the material with both energy dissipation and self-repair capabilities, forming the molecular basis for its high tear resistance and low permanent deformation even at low densities.
[0053] In summary, the lightweight polyurethane filled tire of the present invention constructs a honeycomb-like wall structure through a composite nanofiber network and combines it with reversible coordination crosslinking of metal-carboxylate groups, which solves the problems of insufficient load-bearing capacity, easy brittleness and poor durability of lightweight porous materials, and achieves high performance while significantly reducing weight.
[0054] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0055] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be noted that due to the limitations of textual expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of the present invention.
Claims
1. A lightweight polyurethane-filled tire, comprising a tire carcass and a polyurethane elastomer composite material filled within the carcass, characterized in that, The polyurethane elastomer composite material comprises: A polyurethane matrix, wherein the polyurethane matrix contains metal cations; A composite nanofiber network uniformly dispersed in the polyurethane matrix is formed by the self-assembly of carboxylated cellulose nanocrystals and para-aramid nanofibers through hydrogen bonding and / or electrostatic interaction, and the composite nanofiber network is wrapped around the surface of lightweight microspheres to form a honeycomb-like wall structure. The surface of the carboxylated cellulose nanocrystals is rich in carboxylate groups; the metal cations form coordination bonds with the carboxylate groups on the surface of the carboxylated cellulose nanocrystals to form a non-covalent crosslinked network in the polyurethane elastomer composite material.
2. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The carboxylated cellulose nanocrystals were prepared by selectively oxidizing the primary hydroxyl groups at the C6 position on the surface of the cellulose nanocrystals to sodium carboxylate groups using the TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical) oxidation system.
3. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The para-aramid nanofibers are prepared by deprotonating and exfoliating para-aramid fibers in a dimethyl sulfoxide / potassium hydroxide system to obtain para-aramid nanofibers with a diameter of 5-30 nm and an aspect ratio greater than 500, and the surface of the nanofibers retains amide groups.
4. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The lightweight microspheres are selected from one or a combination of two types: the first type is expanded thermoplastic polymer microspheres with a shell of vinylidene chloride-acrylonitrile copolymer, a particle size of 20~100μm, and a density of 0.1~0.2g / cm³. 3 ; The second type consists of hollow glass microspheres or hollow ceramic microspheres, with a particle size of 10~80μm and a density of (0.15~0.4)g / cm³. 3 The compressive strength is greater than 20 MPa.
5. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The metal cation is Zn. 2+ Ca 2+ Mg 2+ Fe 3+ Or Al 3+ One or more of the following; the metal cation is introduced in the form of acetylacetone salt, chloride or sulfate.
6. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The polyurethane matrix is prepared by reacting an isocyanate prepolymer with a curing agent component. The isocyanate prepolymer is a reaction product of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, or isophorone diisocyanate with a polyether polyol or a polyester polyol.
7. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The mass ratio of the carboxylated cellulose nanocrystals to the para-aramid nanofibers is 1:(0.5~5), the total mass of the composite nanofiber network accounts for 1%-10% of the total mass of the polyurethane elastomer composite material, and the volume of the lightweight microspheres accounts for 20%-60% of the total volume of the polyurethane elastomer composite material.
8. A method for preparing a lightweight polyurethane-filled tire according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Preparation of carboxylated cellulose nanocrystals: Cellulose nanocrystals were dispersed in water to form a suspension. Under the conditions of TEMPO / sodium bromide / sodium hypochlorite oxidation system, pH 9-11, and room temperature, the primary hydroxyl groups at the C6 position on the surface of the nanocrystals were selectively oxidized to sodium carboxylate groups. After dialysis and freeze drying, carboxylated cellulose nanocrystals were obtained. (2) Preparation of para-aramid nanofibers: Para-aramid short-cut fibers were added to a dimethyl sulfoxide / potassium hydroxide system and stirred under nitrogen protection at room temperature for deprotonation and exfoliation. After precipitation and washing, a para-aramid nanofiber suspension was obtained. (3) Constructing a composite nanofiber network and coating lightweight microspheres: The carboxylated cellulose nanocrystal suspension obtained in step 1 and the para-aramid nanofiber suspension obtained in step 2 are mixed at a mass ratio of 1:(0.5~5) and ultrasonically treated at pH 8~9 to allow the carboxylated cellulose nanocrystals and para-aramid nanofibers to self-assemble into a composite nanofiber network through hydrogen bonding and / or electrostatic interaction; lightweight microspheres are added under stirring to allow the composite nanofiber network to adsorb and coat the surface of the lightweight microspheres, and the carboxylated cellulose nanocrystals and para-aramid nanofibers complement each other to form a fiber shell. The fiber shells on the surfaces of adjacent microspheres are interconnected to form a precursor slurry with a honeycomb-like structure; the slurry is vacuum dried to obtain the composite microsphere filler; (4) Preparation of polyurethane elastomer composite material and filling of tire: The composite microsphere filler obtained in step (3) is mixed evenly with the curing agent component containing metal cations, isocyanate prepolymer is added, vacuum stirring is performed to remove bubbles, and the mixture is injected into a mold placed in the tire cavity and heated to cure. During the curing process, the metal cations form coordination bonds with the carboxylate groups on the surface of carboxylated cellulose nanocrystals to form a non-covalent cross-linked network, thus obtaining the lightweight polyurethane filled tire.
9. The lightweight polyurethane-filled tire according to claim 1, characterized in that, The curing temperature in step (4) is 60~90℃ and the curing time is 12~48 hours.
10. The application of the lightweight polyurethane-filled tire according to any one of claims 1 to 7 in a low-speed, high-load vehicle, the low-speed, high-load vehicle including forklifts, loaders, mining dump trucks or airport ground support vehicles.
